Efficient, highly diastereoselective MS 4 Å-promoted one-pot, three-component synthesis of 2,6-disubstituted-4-tosyloxytetrahydropyrans via Prins cyclization - Ahmed, Naseem; Konduru, Naveen Kumar (Beilstein Journal of Organic Chemistry, 2012)
A simple, efficient and highly diastereoselective one-pot three-component synthesis of functionalized 2,6-disubstituted-4-tosyloxytetrahydropyrans was performed. The synthesis features an optimized Prins cyclization in which an aromatic homoallylic alcohol, an aromatic/aliphatic aldehyde, and p-toluenesulfonic acid (catalyst and reagent) are reacted in the presence of molecular sieves (MS) 4 Å at reflux in dichloromethane to afford excellent yields (72–96%) within short reaction times (20–90 min). The MS 4 Å-promoted synthesis proved to be versatile enough to provide an array of symmetrical and unsymmetrical tetrahydropyran derivatives in economical manner. Furthermore, cleavage of the 4-tosyl group under mild conditions afforded 4-hydroxytetrahydropyran in excellent yields (95–96%).
Keywords: aromatic homoallylic alcohols; 2,6-disubstituted-4-tosyloxytetrahydropyrans; MS 4 Å; Prins cyclization; PTSA